2015
DOI: 10.1016/j.vaccine.2015.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax vaccine recipients lack antibody against the loop neutralizing determinant: A protective neutralizing epitope from Bacillus anthracis protective antigen

Abstract: Background Epitope-focused immunogens can elicit antibody against the loop neutralizing determinant (LND), a neutralizing epitope found within the 2β2-2β3 loop of protective antigen (PA), which can protect rabbits from high-dose inhalation challenge with Bacillus anthracis Ames strain. Interestingly, data suggests that this epitope is relatively immunosilent in rabbits and non-human primates immunized with full length PA. Methods To determine whether the LND is immunosilent among humans vaccinated with PA, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Thus, those host populations with lower mortality (kudu in ENP and zebra in KNP) are more likely to be exposed to sublethal amounts of the pathogen based on their foraging behavior and the relative risk of that behavior in the two landscapes ( 43 , 44 , 51 ), yet show greater toxin neutralization than their counterparts in the other park. A previous study showed that animals that were immunized with antigens of spore origin conferred protection against B. anthracis through the production of antibodies that reduced spore germination ( 83 ). This type of sublethal natural “immunization” may have induced anti-spore antibodies and reduced germination in zebra in KNP and kudu in ENP ( 84 ), but this hypothesis would need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, those host populations with lower mortality (kudu in ENP and zebra in KNP) are more likely to be exposed to sublethal amounts of the pathogen based on their foraging behavior and the relative risk of that behavior in the two landscapes ( 43 , 44 , 51 ), yet show greater toxin neutralization than their counterparts in the other park. A previous study showed that animals that were immunized with antigens of spore origin conferred protection against B. anthracis through the production of antibodies that reduced spore germination ( 83 ). This type of sublethal natural “immunization” may have induced anti-spore antibodies and reduced germination in zebra in KNP and kudu in ENP ( 84 ), but this hypothesis would need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, cAb29 stabilizes an exposed conformation that is sampled by the D2L2 loop without the antibody. Consequently, our results provide a mechanistic basis for using the D2L2 as a target for developing anthrax vaccinations aimed at eliciting the formation of effective neutralizing antibodies [14,28,29].…”
Section: Discussionmentioning
confidence: 83%
“…Taken together, cAb29 stabilizes an exposed conformation that is sampled by the D2L2 loop without the antibody. Consequently, our results provide a mechanistic basis for using D2L2 as a target for the development of anthrax vaccines aimed at eliciting the formation of effective neutralizing antibodies (Oscherwitz et al, 2015;McComb & Martchenko, 2016;Yin et al, 2008).…”
Section: Discussionmentioning
confidence: 85%